2020
DOI: 10.1002/asia.201901620
|View full text |Cite
|
Sign up to set email alerts
|

RhIII‐Catalyzed Synthesis of Highly Substituted 2‐Pyridones using Fluorinated Diazomalonate

Abstract: AR h III -catalyzed strategy wasd eveloped for the rapid constructiono fh ighly substituted 2-pyridones caffolds using a,b-unsaturated oximes and fluorinated diazomalonate. The reaction proceeds through direct, site-selective alkylation based on migratory insertiona nd subsequent cyclocondensation. Awide substrate scope with different functional groups wase xplored. The requirement of fluorinated diazomalonate was explored for this transformation. The developed methodology was furthere xtended with the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…The method proceeded via i) the site-selective alkylation of the α, βunsaturated oxime using fluorinated diazo malonate as an alkylating agent ii) nucleophilic attack of oxime N-center towards the highly electrophilic ester carbonyl centre and iii) subsequent rearomatization (Scheme 9). [21] This protocol featured a vast scope, including aryl groups with electrondeficient, electron-withdrawing substituents, and functional groups such as esters and halides.…”
Section: Construction Of Highly Substituted 2-pyridone Derivativesmentioning
confidence: 99%
“…The method proceeded via i) the site-selective alkylation of the α, βunsaturated oxime using fluorinated diazo malonate as an alkylating agent ii) nucleophilic attack of oxime N-center towards the highly electrophilic ester carbonyl centre and iii) subsequent rearomatization (Scheme 9). [21] This protocol featured a vast scope, including aryl groups with electrondeficient, electron-withdrawing substituents, and functional groups such as esters and halides.…”
Section: Construction Of Highly Substituted 2-pyridone Derivativesmentioning
confidence: 99%
“…Lastly, a nucleophilic attack of the N-atom present on oxime to the electrophilic carbonyl center present on trifluoroethyl ester occurred followed by deprotonation provided the desired cyclized 2-pyridone product (148). [51] Volla and co-workers demonstrated a method to synthesize biologically relevant indolo[2,3-c]isoquinoline-5-ones (155) derivatives via Rh(III)-catalyzed reaction of N-methoxy benzamides (153) and 3-diazoindolin-2-imines (154) under modest reaction conditions (Scheme 41). [52] During this study, they have screened [Cp*RhCl 2 ] 2 as a catalyst along with different bases and solvents, and found that reaction gave maximum yield of product (155) when employed CsOAc as a base in DCE at 80 °C.…”
Section: Synthesis Of N-containing Heterocyclesmentioning
confidence: 99%
“…Samanta et al developed an economic process for the synthesis of 2-pyridone scaffolds (148) via cycloaddition of α, β-unsaturated oximes (146) with fluorinated diazomalonate (147) using (Cp*RhCl 2 ) 2 as a catalyst (Scheme 40). [51] After having optimized reaction conditions i. e., 1 equiv. of 2-pyridone and 1.2 equiv.…”
Section: Synthesis Of N-containing Heterocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reagents and starting materials were purchased from Sigma-Aldrich, TCI, Avra, Spectrochem, and other commercially available sources, used without further purification unless otherwise noted. All aldol condensation derivatives, 28 imine derivative, 29 and alkyne derivatives 30 were prepared according to the reported literature procedure.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%